CORRELATION OF LIPID PEROXIDE -MALONDIALDEHYDE LEVEL WITH DURATION OF DIABETES MELLITUS (TYPE 2) - DR.A.J.MANJULA DEVI,; DR.S.SRIDEVI,; DR.SHANTHI.B,; DR.RATHIROOPAVATHY, (International Journal of Pharma and Bio Sciences, 2014)
Type 2 diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia and oxidative stress which occurs as a result of imbalance between pro-oxidants and antioxidants. Malondialdehyde (MDA) is a product of the peroxidation and it is considered to be one of the markers of oxidative stress. The association between DM duration and MDA levels in type 2 DM remains controversial. This study was undertaken to evaluate the correlation between MDA levels and DM duration. To compare the oxidative stress in two study groups MDA levels were compared. The mean MDA levels were high in diabetics with duration more than 5 years. The same was compared between the two study groups (Group I-Duration of DM < 5 years & Group II-Duration of DM > 5 years) using student t test. The difference in MDA levels between two diabetic groups was significant (P<.01).But the comparison of long term glycemic control (HbA1C) between two diabetic groups was not statistically significant. This suggests that oxidative stress might be related to duration of DM irrespective of glycemic control. The correlation study of MDA levels with the duration of diabetes and glycemic control (HbA1C) showed that the levels were statistically significant for the duration of DM and not statistically significant for glycemic control.